2016
DOI: 10.17795/jjcdc.40063
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Religious Coping in Perception of Suffering among Patients Undergoing Dialysis

Abstract: Background: Chronic kidney disease is a threatening condition for the health, economic and social status of the affected person, his/her family and society. Objective: With regard to the mental and health issues that patients undergoing dialysis encounter, the current study aimed to examine the role of religious coping in perception of suffering among these patients. Methods: The current correlational study had a statistical population including all patients undergoing dialysis referred to Aliibn-Abi-Talib (AS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The results of studies conducted in Iran indicate that religious and spiritual practices improve the psychological well-being and quality of life of patients with chronic diseases, e.g. multiple sclerosis [ 40 ], reduce mental tension in patients who receive dialysis [ 41 ], and facilitate adaptation [ 42 ] and self-care [ 43 ] in patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The results of studies conducted in Iran indicate that religious and spiritual practices improve the psychological well-being and quality of life of patients with chronic diseases, e.g. multiple sclerosis [ 40 ], reduce mental tension in patients who receive dialysis [ 41 ], and facilitate adaptation [ 42 ] and self-care [ 43 ] in patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The HSS consisted of 29 items indicating the severity of stressors associated with the hemodialysis procedure as perceived by patients. HSS is rated based on a four-point Likert scale ranging from not at all (1) to a great deal (4). The score range is 29 -116 for the total scale, 23 -92 for the 23 psychosocial items, and 6 -24 for the six physiological items (1).…”
Section: Inclusion/exclusion Criteriamentioning
confidence: 99%
“…End-stage renal disease (ESRD) is the result of chronic renal failure. It is an irreversible clinical condition in which the patient needs alternative renal therapies to avoid uremia (4). In this regard, the head of the Department of Transplantation and Special Diseases in the Ministry of Health reported that the growth rate of patients with kidney diseases in Iran during the last 10 years has been 14% and dialysis patients' growth rate has been 12% (5).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic diseases make life very difficult and patients dealing with such diseases face many challenges in reaching an acceptable level of health and physical, mental, and social functioning (6). Thalassemia is associated with a wide range of serious psychological and clinical challenges.…”
Section: Introductionmentioning
confidence: 99%